Clinical Informatics Board Review and Self Assessment (Springer International Publishing, 2018)
The book offers an introduction to all the informatics concepts that are represented on the Clinical Informatics Board Examination The core and direction of this book is to mirror the model of clinical informatics which is used by the American Board of Preventive Medicine to create their exam. Unlike any other text on the market, the book includes simulated exam questions, to help the reader asses his knowledge and focus his study. Clinical Informatics Board Review and Self Assessment is a thorough practical assistant to refine the reader's knowledge regarding this youngest and possibly broadest fields of medicine.